Answer:
Explanation:
It is possible to answer this question knowing Hess's law that says you can sum half-reactions enthalpy cahnge to obtain enthalpy change of the total reaction. Using the reactions:
<em>(1) </em>2NO(g) → N₂(g)+O₂(g) ΔH = -180,6 kJ
<em>(2) </em>N₂(g) + O₂(g) + Cl₂(g) → 2NOCl(g) ΔH = +103,4 kJ
The reverse reactions of (1) and (2) are:
<u>N₂(g)+O₂(g)</u> → 2NO(g) ΔH = +180,6 kJ
2NOCl(g) → <u>N₂(g) + O₂(g)</u> + Cl₂(g) ΔH = -103,4 kJ
The sum of these reactions is:
2NOCl(g) → 2NO(g) + Cl₂(g) ΔH = +180,6 kJ -103,4 kJ = <em>77,2 kJ</em>
<em />
I hope it helps!